1997
DOI: 10.1021/jp970041q
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid ab Initio QM/MM Simulation of N-Methylacetamide in Aqueous Solution

Abstract: Combined quantum mechanical and molecular mechanical (QM/MM) simulations of N-methylacetamide in aqueous solution have been carried out to investigate the charge polarization of the solute and to explore the feasibility of hybrid QM/MM calculations using ab initio methods. In the present study, the ab initio Hartree−Fock theory along with the 3-21G basis set was used in the quantum mechanical calculations. Statistical mechanical Monte Carlo approach was then applied in molecular mechanical simulations, employi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
103
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 117 publications
(126 citation statements)
references
References 74 publications
23
103
0
Order By: Relevance
“…More interesting is the fact that, in average, the nitrogen atom does not accept any hydrogen bond from water molecules. Similar results have been found by Gao et al in a QMrMM simulation of formamide 39 and by us in a classical Molecular Dynamics simulation of the N-methylazetidinone derivative. 26 It is interesting to note that previous studies on ␤-lactam᎐water complexes 23 also show the trend of water molecules to solvate the carbonyl oxygen preferentially.…”
Section: Dynamics In Aqueous Solution: Rigid Solutesupporting
confidence: 90%
“…More interesting is the fact that, in average, the nitrogen atom does not accept any hydrogen bond from water molecules. Similar results have been found by Gao et al in a QMrMM simulation of formamide 39 and by us in a classical Molecular Dynamics simulation of the N-methylazetidinone derivative. 26 It is interesting to note that previous studies on ␤-lactam᎐water complexes 23 also show the trend of water molecules to solvate the carbonyl oxygen preferentially.…”
Section: Dynamics In Aqueous Solution: Rigid Solutesupporting
confidence: 90%
“…39,40 Monte Carlo QM/MM studies using MOPAC have been reported and the results obtained are very encouraging. 41,42 In the present QM/MM version of DIADORIM program the semiempirical program MOPAC 6 was introduced as a subroutine of the main Monte Carlo code. Therefore, all the Hamiltonian models and other facilities implemented in the MOPAC program can be used to calculate the energy and other information for a given molecule or cluster along the phase space sampling.…”
Section: The Intramolecular Energymentioning
confidence: 99%
“…Several relatively new functionals 108,109 including a dependence on kinetic energy density and having improved performance for barrier heights and noncovalent interactions have not yet seen use for enzyme simulations. Although first principles methods such as DFT are very appealing even when combined with MM, [289][290][291][292] they are still too slow to allow sufficient sampling of the enormous number of enzyme conformational states to obtain the potential of mean force along the reaction coordinate. In fact, the ability to sample enzyme conformational space is the second most important issue in computational studies of enzymatic reactions.…”
Section: 23mentioning
confidence: 99%